2023
DOI: 10.7759/cureus.37739
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Cancer Knowledge and Awareness Among Women in Makkah Region, Saudi Arabia

Abstract: Introduction: Thyroid cancer (TC) is the most prevalent endocrine cancer, and it has shown a rapid rise in incidence across the globe in recent decades. This study aimed to evaluate the level of knowledge about TC among women in the Makkah Region, Saudi Arabia. Methods: A cross-sectional study was conducted between 28 December 2022 and 20 January 2023 among women in the Makkah Region via a self-administrated online questionnaire using Google Forms. Our inclusion criteria were women aged 18 years and older from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Individuals without TC had higher knowledge scores in recognizing the benign nature of most TNs, the limited occurrence of malignancy, and the necessity for fine-needle aspiration biopsy. These insights were consistent with public awareness efforts and educational campaigns targeted at dispelling fears and misconceptions surrounding TNs (28). However, the lower correct rates regarding ultrasound-guided fine-needle aspiration biopsy and levothyroxine (L-T4) therapy for normal thyroid function indicated potential gaps in understanding more nuanced aspects of TN management.…”
Section: Discussionsupporting
confidence: 55%
“…Individuals without TC had higher knowledge scores in recognizing the benign nature of most TNs, the limited occurrence of malignancy, and the necessity for fine-needle aspiration biopsy. These insights were consistent with public awareness efforts and educational campaigns targeted at dispelling fears and misconceptions surrounding TNs (28). However, the lower correct rates regarding ultrasound-guided fine-needle aspiration biopsy and levothyroxine (L-T4) therapy for normal thyroid function indicated potential gaps in understanding more nuanced aspects of TN management.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, in the Asir region study, the belief in no cure was only among 14.9% of individuals [10]. In contrast, a study conducted among women in Makkah regarding thyroid cancer reported that 56% of ladies believed it to be incurable [14]. Advanced treatment options, research studies, and public awareness can reduce the mortality rates of thyroid cancer.…”
Section: Discussionmentioning
confidence: 94%
“…In terms of awareness campaigns, only 10.1% had attended some special thyroid cancer campaign or watched it. Most of the participants of research on thyroid cancer awareness in Makkah reported a similarly low rate [14]. This emphasizes the need for more effective campaigns and special awareness programs against thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation